(untitled) (Journal of Atomic and Molecular Sciences, 2010)
We present a physics scheme for transferring an unknown atomic entangled state via cavity QED. In the transfer process the interaction between atoms and a single-mode nonresonant cavity with the assistance of a strong classical driving field (substitute) replace the Bell-state measurements. The scheme is insensitive to both the cavity decay and the thermal field. In addition, the success probability can reach 1.0 in our scheme.